Insight into photon conversion of Nd3+ doped low temperature grown p and n type tin oxide thin films. Issue 71 (14th July 2016) - Bouras, K.; Schmerber, G.; Aureau, D.; Rinnert, H.; Ferblantier, G.; Fix, T.; Colis, S.; Bazylewski, P.; Leedahl, B.; Etcheberry, A.; Chang, G. S.; Dinia, A.; et al.
Abstract : p and n type SnO x thin films are successfully functionalized with optically active Nd 3+ ions for efficient UV photon conversion. Abstract : The synthesis of multifunctional high-quality oxide thin films is a major current research challenge given their potential applications. Herein, we report on p and n type tin oxides thin films as functional TCOs with photon management properties through doping with Nd 3+ rare earth ions. We show that the structure, composition, carrier transport and optical properties of the sputtered Nd:SnO x films can be easily tuned by simply varying the Ar/O2 gas flow ratio ( R ) during the deposition step. The increase of the oxygen content leads to drastic changes of the material properties from p-type SnO to n-type SnO2 . Furthermore, all Nd:SnO x films are found to be highly conductive with resistivities as low as 1 × 10 −3 Ω cm −1 and carrier mobilities up to 129 cm 2 V −1 s −1 . Thanks to deep XPS and NEXAFS spectroscopies, we gained insight into the coordination and oxidation degrees of the elements within the matrices. The insertion and optical activation of the incorporated Nd 3+ ions have been successfully achieved in both matrices. As a consequence, strong NIR luminescence lines, typical of Nd 3+ ions, were recorded under UV laser excitation. We experimentally show that the efficient Nd 3+ photoluminescence in the near infrared region originates from efficient sensitization from the host matrix, through energy transfer. We found that the SnO2 host matrix provides more efficient sensitization of Nd 3+ as compared to the SnO matrix. An energy transfer mechanism is proposed to explain the observed behaviour.